Geochemistry and geochonology U-Pb and Sm/Nd data of the orthogneiss from Pontalina region (GO), Brazil - Beltran Navarro, Guillermo Rafael [UNESP]; Zanardo, Antenor [UNESP]; Conceicao, Fabiano Tomazini da [UNESP]; Montibeller, Cibele Carolina [UNESP] (Soc Brasileira Geologia, 2013)
Orthogneisses of tonalitic to granodioritic composition with calc-alkaline, metaluminous to peraluminous characteristics crop out at the region of Pontalina. The orthogneisses exhibit negative anomalies of Nb, Ta, P and Ti relative to rare earth elements (REE) and litophile elements, besides low contents of Nb, Ta, Y and Yb, similar to the rocks formed in subduction environments. U-Pb geochronological data show a neoproterozoic (681.5 +/- 7.7 Ma) crystallization for the orthogneisses. The Nd isotope data yielded weakly negative to positive epsilon(Nd)(T) (+3.2 up to -0.1), with T-DM model ages of similar to 1.2 Ga. The combined geochemical and isotopic data suggest that the protolith of these orthogneisses are representative of neoproterozoic juvenile magmas, probably developed in an island arc system, generated during a ca.700 and 600 Ma event of crustal accretion in the western edge of the Sao Francisco Craton.
Keywords: geochemistry; geochronology; orthogneiss; Goias magmatic arc